Effect of a Nutrition Support Formula in Adults With Inflammatory Bowel Disease: A Pilot Study - Jennifer J Ryan ND, MS; Douglas A Hanes PhD; Ryan D Bradley ND, MPH; Nikhat Contractor PhD (SAGE Publishing, 2019)
Background Due to the high prevalence of nutrient deficiencies in patients with inflammatory bowel disease (IBD), routine monitoring of nutrient status and supplementation are recommended. Objective This preliminary study was implemented to prospectively identify potential effects of a nutrition support formula on blood nutrient parameters in adults with IBD. Methods Ten adults with Crohn's disease or ulcerative colitis were recruited from the Portland, Oregon, metropolitan area into a single-arm, open-label pilot study. Participants consumed a nutrition support beverage twice daily for 12 weeks. The formula contained a mixture of micronutrients (including methylated forms of folate and vitamin B12), macronutrients, and phytonutrients (including curcumin, xanthohumol, ginger compounds, and quercetin). Primary measures were the following parameters: folate, vitamin B12, red blood cell (RBC) count, hemoglobin, hematocrit, electrolytes, and albumin. Exploratory measures included a food frequency questionnaire, circulating blood cell counts, and inflammatory markers. Results Nine participants completed the study and one withdrew. Adherence was 98%. Serum folate increased 48.7% ( P  = .029), serum vitamin B12 increased 17.4% but did not reach statistical significance ( P  = .053), and red cell distribution width (RDW) decreased 9.2% ( P  = .012) over the 12-week study period. There were minimal shifts in total white blood cell (WBC) counts (−1.0%, P  = .845), but percent neutrophils decreased 10.4% ( P  = .042) and absolute lymphocyte count increased 18.6% ( P  = .048). RBC count, hemoglobin, hematocrit, electrolytes, albumin, and inflammatory markers did not change significantly. Post hoc analysis demonstrated that neutrophil-lymphocyte ratio (NLR) decreased 18.4% (not significant, P  = .061). Conclusion Serum folate and RDW improved in adults with IBD after 12 weeks. Modulation of leukocyte subtypes was also observed, including a decrease in neutrophils and an increase in lymphocytes, with no change in total WBC count. A randomized, controlled study to further examine effects of the nutrition support formula will be initiated to follow up on this promising, but preliminary investigation.